2001
DOI: 10.1029/2000gl012378
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and related gaseous pollutants in the boundary layer of eastern China: Overview of the recent measurements at a rural site

Abstract: Abstract. We present a summary of the latest measurements of ozone (03)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(100 citation statements)
references
References 22 publications
10
89
1
Order By: Relevance
“…In the afternoon, the PBL O 3 concentrations reached the daily maximum at 13:00-14:00 LT in summer but at 15:00-16:00 LT on annual average. The afternoon maximum of PBL O 3 is a typical feature downwind of an urban area, and the peak time often depends on the distance from the city (Logan, 1989;Wang et al, 2001Wang et al, , 2005Wang et al, , 2006a. The diurnal variation of MOZAIC O 3 in the lower PBL is similar to those measured in summer 2005 at a mountainous site about 50 km north of the center of Beijing (Wang et al, 2006a).…”
Section: Diurnal Variation Of Lower Tropospheric Osupporting
confidence: 59%
See 1 more Smart Citation
“…In the afternoon, the PBL O 3 concentrations reached the daily maximum at 13:00-14:00 LT in summer but at 15:00-16:00 LT on annual average. The afternoon maximum of PBL O 3 is a typical feature downwind of an urban area, and the peak time often depends on the distance from the city (Logan, 1989;Wang et al, 2001Wang et al, , 2005Wang et al, , 2006a. The diurnal variation of MOZAIC O 3 in the lower PBL is similar to those measured in summer 2005 at a mountainous site about 50 km north of the center of Beijing (Wang et al, 2006a).…”
Section: Diurnal Variation Of Lower Tropospheric Osupporting
confidence: 59%
“…Wang et al (2001) showed an early summer maxima of surface O 3 (in May) at Lin'an, in centraleastern China just before the rainy season starts in that region, while southern China had an annual maximum in autumn (Lam et al, 2001;Wang et al, 2005). The different seasonal patterns can be explained by distinct meteorological conditions in different parts of China.…”
Section: Diurnal Variation Of Lower Tropospheric Omentioning
confidence: 99%
“…Similarly, annual averaged NO 2 concentration 5.3 ppb was for 3 years period with highest annual NO 2 concentration 5. than the rate of increase of NO x 6.5 % year −1 in India between 2000 reported by Streets et al (2003). The O 3 concentrations linearly depend on emission of NO x in the rural sites (Wang et al 2001). It is seen from the …”
Section: Methodsmentioning
confidence: 52%
“…comm., 2002). The Linan site is located approximately 10 km north of the Linan county township (population B50,000), 50 km northwest of Hangzhou and 250 km southwest of Shanghai (Luo et al, 2000;Wang et al, 2001; location labeled in Fig. 2).…”
Section: Comparison Of Modeled Isoprene Fluxes With Fluxes Inferred Fmentioning
confidence: 99%